'Get paid, get out': online resistance to call centre labour in Canada. (17th December 2018) - Johnston, Matthew S.; Johnston, Genevieve; Sanscartier, Matthew D.; Ramsay, Mark
Abstract : This qualitative content analysis of 503 anonymous online reviews of 52 Canadian call centres posted on RateMyEmployer.ca explores how forms of resistance, alienation and emotional labour are expressed outside of the workplace. Our study finds that digital publics are producing emotive insurgencies and networks of support within marginalised communities that undermine employers' attempts at deadening the workforce. The reviews exemplify worker awareness of exploitation as some connect these issues to broader socio‐economic factors that are beyond their control. While many offer tactics to challenge and destabilise their working conditions and culture as well as heartfelt and sarcastic warnings of what one might expect if they pursue call centre employment, others use the online space as a means of venting frustrations, eliciting empathies and expressing sentiments of hope(lessness).